Single-ventricle palliation in children with atrioventricular septal defect and transposition of the great arteries: 45 years of experience. (29th August 2020) - Buratto, Edward; Fricke, Tyson A.; Ye, Xin Tao; Brink, Johann; Brizard, Christian P.; d'Udekem, Yves; Konstantinov, Igor E.
Abstract: Background: The association of atrioventricular septal defect and transposition of the great arteries is very rare. As a rule, these patients have unbalanced ventricles. However, there have been no studies describing the results of single-ventricle palliation in these children. Methods: All children who underwent surgery with a diagnosis of atrioventricular septal defect and transposition of the great arteries were included in the study. Data were obtained from medical records. Results: A total of 38 patients with atrioventricular septal defect and transposition of the great arteries underwent single-ventricle palliation at the study institution between 1971 and 2016. The mean follow-up was 12.4 years (median: 14.6 years, range 2–43.3 years). Most children had unbalanced atrioventricular septal defect (94.7%, 36/38). Survival was 67.6% (95% confidence interval [CI]: 50.0–80.2%) at 10 years and 57.8% (95% CI: 38.0–73.4%) at 20 years. By 10 years, 58.6% (95% CI: 40.8–72.7%) had progressed to Fontan completion, while 32.5% (95% CI: 18.2–47.6%) had died. In patients achieving Fontan completion, 20-year event-free survival was 73.3% (95% CI: 34.8–91.3%), while 5.0% (95% CI: 0.4–20.5%) had undergone cardiac transplantation and 21.7% (95% CI: 3.2–50.8%) had undergone takedown of the Fontan circulation. Freedom from atrioventricular valve surgery was 57.0% (95% CI: 37.2–72.7%) at 10 and 20 years. Conclusions: The association of atrioventricular septal defect and transposition of the great arteries is very rare, and most of these children have unbalanced ventricles. Single-ventricle palliation results in 25-year overall survival of 50%. However, in patients, who had Fontan completion, survival was 75% at 25 years after Fontan operation.